ظواهر مُختارة من لهجة ميلة؛ دراسة صوتية صرفية - سراوي, سهام; مسيلي, وردة (جامعة الوادي - University of Eloued, 2021)
يهدف البحث الموسوم" ظواهر مختارة من لهجة ميلة ؛ دراسة صوتية صرفية" إلى تسليط الضوء على الأهمية العلمية للتوجه اللّهجي للهجات في الوطن العربي عموما و اللّهجة المحلية الجزائرية خصوصا، والتعرف على فرعٍ جديدٍ في اللغويات؛ علم اللهجات. يعد من أحدث الاتجاهات في البحوث اللغوية وتناولها بالدرس والتحليل والكشف عن أسرارها وتناولها تناولا أكاديميا. محاولين الإجابة على إشكال مفاده دراسة لهجة محلية من لهجات الشرق الجزائري؛ لهجة ميلة واستقصاء أهم التغيرات والخصائص اللغوية التي تتميز بها اللهجة المدروسة على المستويين الصوتي والصرفي. فالبحث الذي بين أيدينا قام على دراسة ميدانية، اتبعنا فيها خطوات دراسة اللّهجة، باختيارنا منطقة ميلة أنموذجا مع الاعتماد على الجانب الوصفي مما جعلنا نتبع المنهج الوصفي التحليلي في وصف الظواهر اللغوية بأخذها عن أفواه الناطقين الأصليين وتمثيلها تمثيلا صحيحا عن طريق المشافهة المباشرة من أحاديث عفوية. الكلمات المفتاحية: ظواهر، لهجة، ميلة ، صوتية، صرفية Abstract The research entitled "Selected Phenomena of the Mila Dialect; a morphological phonological study" aims to shed light on the scientific importance of the dialectical orientation of the dialects in the Arab world in general and the local Algerian dialect in particular, and to identify a new branch of linguistics. dialectology. It is considered one of the latest trends in linguistic research, dealing with it by studying, analyzing, revealing its secrets, and dealing with it academically. Trying to answer the problem of studying a local dialect of the eastern dialects of Algeria; The Mila dialect and the investigation of the most important changes and linguistic characteristics that characterize the studied dialect at the phonemic and morphological levels. The research in our hands was based on a field study, in which we followed the steps of studying dialect, by choosing the Mila region as a model with reliance on the descriptive aspect, which made us follow the descriptive and analytical approach in describing linguistic phenomena by taking them from the mouths of native speakers and representing them correctly by direct verbal communication from spontaneous conversations. Key words: Phenomena, Dialect, Mila, phonemic, morphologica
مقال
Keywords: ظواهر، لهجة، ميلة ، صوتية، صرفية